Empowerment of Farmer Communities through Education and Training in the Diversification of Processed Glutinous Rice Products: Economy Empowering in Ciamis Regency West java - Rusdiana, A.; Suryani, Yani; Mulyawan, Setia (Advances in Social Sciences Research Journal, 2025)
Community empowerment becomes significant to do, considering the phenomenon of the Cinyasagvillage Communityare considered not to be able to empower it’sregion potential as a local potential with high economic value. This study aims to identify community empowerment programs to realize a resilient and competitive economy based on local potential. The research method used is the action research method. Based on the root of the problem and in accordance with the action research cycle consisting of design, action, observation and reflection. The results of this study indicate that education and training in the diversification of processed glutinous rice products can increase total turnover of production and increase economic income of the farming community. This study recommends that; to create a resilient and competitive economy based on local potential, the community needs to be empowered and equipped with knowledge management, abilities, skills, and entrepreneurial motivation. If, the production of "OpakMandiriCinyasag", wants to survive more in marketing, it can learn from Opak Oded small and medium enterprise in ConggeangSumedang by implementing Customer Relationship Management